PENERAPAN METODE REGRESI LINEAR DALAM MEMPREDIKSI DATA PENJUALAN BARANG DI TOKO BANGUNAN VITA VIYA - Reno Supardi (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2020)
Abstract- Vita Viya lumberyard is one of the lumberyard is located on Semangka Street, Bengkulu city. During this time the processing sales data of goods in lumberyard is still done conventionally, namely using sales notes that occur every day. Then, the note data will be made into bookkeeping to find out how many sales of goods occur every month. Management of inventory also only sees the remaining items available in the lumberyard without looking at the sales of the item. The problem that often occurs in Vita Viya lumberyard is the management of inventory, where the building materials have a usage period so that they are not suitable for sale. The application in predicting sales data of goods in Vita Viya lumberyard was made by using the Visual Basic.Net programming language by applying the linear regression method. With the construction of the application can be used as an alternative in predicting the sales data of goods in the following month based on sales data that occurred in the last 2 years starting from January 2017 to December 2018. The 2-year data will be used as a data trend to determine the predicted value of goods sold at 1 year in the future. Based on the testing that has been done, it can be concluded that the application is able to predict the sale of goods for the next 1 year based on sales data that has been inputted previously. Based on the testing of error values using the MAPE and MSE methods, it was found that the error value of the predicted value obtained from the linear regression method used the MAPE method of 0.1244575. While, the result by using the MSE method of 14.25.Â Keywords: Linear Regression Method, Prediction of Vita Viya lumberyard.